Régimes institutionnels de ressources et théorie de la régulation - Frédéric Varone; Stéphane Nahrath; Jean-David Gerber (Revue de la Régulation)
This article postulates that an approach combining political science (policy analysis) and institutional economics (property rights theory) enables the identification of the most relevant regulatory dimensions that explain the (un)sustainable uses of natural and cultural resources. From this starting point, it develops an innovative theoretical framework, that of the institutional resource regime (IRR). This framework is then compared with the corpus of the French theory of regulation (TR, as formalized by M. Aglietta, R. Boyer and A. Lipietz). We develop the idea that one of the major contributions of the IRR framework to the TR from a sustainability perspective is its ability to describe the different configurations of resource regimes and thus to explain, and even predict, their effects on the sustainability of a resource.